Scope of mosques as a potential institution in cyclone prone settlements of Bangladesh - Hossain, Imamur; Utaberta, Nangkula; Othuman Mydin, Md Azree (American-Eurasian Network for Scientific Information, 2016)
Bangladesh is one of the most disaster prone countries in the world where 32% of the country’s total geographic area are the coastal areas. Cyclone is almost a yearly phenomenon in the country. During this disaster, people living in the coastal areas mostly take refuge in the nearby cyclone shelters. In most of the cases, the cyclone shelter acts as a primary school or community center of the settlement. Bangladesh, being a country with Muslims in majority, mosques plays an important part in the daily communal life. Like most of the rural areas in Bangladesh, mosque is one of the paramount physical establishments of the coastal communities. This paper aims to explore the social and physical scopes of utilizing mosques as one of the major disaster management center in the coastal areas.